Correlation between Neurotransmitter Transporter Gene Variants and Childhood Autism Spectrum Disorder: A Case–control Study - Chen Shen; Limeng Shen; Fei Qu; Chenye He; Hong Yu; Zengyu Zhang; Jun Liu (Saudi Journal of Medicine and Medical Sciences)
Objective: This case–control study aimed to determine the correlation between single nucleotide polymorphisms (SNPs) in the neurotransmitter transporter genes SLC6A3 and SLC6A4 and childhood autism spectrum disorder (ASD), as well as the severity of the disease. Patients and Methods: Children with ASD and age- and sex-matched healthy controls were recruited from a hospital and schools, respectively. Seven SNPs in the SLC6A3 gene and three SNPs in the SLC6A4 gene were analyzed in blood cell DNA using the TaqMan probe approach. The severity of the disease was evaluated using the Childhood Autism Rating Scale (CARS). Results: A total of 249 children with ASD and 343 controls were included. The genotype frequencies of the examined SNPs were not correlated with childhood ASD. Only the T allele of the SNP rs140700 displayed a non-significant association with a reduced risk of childhood ASD (OR = 0.6, 95% CI: 0.4–1.0, P = 0.0517). Interestingly, the C allele of rs140701 was significantly correlated with lower disease severity (OR = 0.6, 95% CI: 0.4–0.9, P = 0.0093). Additionally, the genotype of rs27072 was significantly associated with the score of the body use domain of CARS; however, no examined SNPs showed a significant association with the overall score. Conclusion: Certain SNPs on neurotransmitter transporter SLC6A3 and SLC6A4 genes are correlated with the severity of childhood autism spectrum disorder but not with the risk of developing the disease. Further studies are needed to explore the underlying mechanisms and potential clinical applications.